Beyond Conservation: Indonesia's Maritime Security Strategy Against Transnational Wildlife Trafficking as a Non-Traditional Security Threat - Khulfi M Khalwani; Bambang Irwanto (GoAcademica Research & Publishing, 2026)
Wildlife trafficking has evolved beyond a biodiversity conservation issue and increasingly represents a form of transnational maritime crime that threatens national security, environmental sustainability, and governance. As the world's largest archipelagic state and one of the world's megabiodiversity countries, Indonesia faces significant vulnerabilities to wildlife trafficking networks operating through maritime routes and digital platforms. This study aims to formulate strategic policy options for strengthening Indonesia's maritime security response to wildlife trafficking from a non-traditional security perspective. A qualitative descriptive approach was employed using literature review, document analysis, SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis, expert judgment validation, and Suitable, Feasible, Acceptable, and Desirable (SFAD) evaluation. The findings indicate that Indonesia possesses significant strengths, including a comprehensive legal framework, specialized institutions, and international cooperation mechanisms. However, institutional fragmentation, limited intelligence integration, and uneven enforcement capacity remain major challenges. The SFAD assessment identifies the establishment of a National Wildlife Crime Intelligence Fusion Center and an Integrated Maritime Wildlife Enforcement Task Force as the highest-priority strategic options. Based on these findings, this study proposes an Integrated Maritime Wildlife Security Strategy (IMWSS) comprising five pillars: intelligence integration, integrated maritime enforcement, technology-based digital surveillance, financial investigation and asset recovery, and regional cooperation. The study concludes that wildlife trafficking should be addressed as a maritime security issue rather than solely a conservation concern and provides a practical framework for strengthening Indonesia's response to transnational wildlife trafficking.